STRATEGY OF POST- CRISIS ECONOMIC DEVELOPMENT: A COMPARATIVE STUDY BETWEEN MEDINA CITY STATE 622-623 AND TURKEY 2008-2009 - Adib Lutfi (: 2621-0924)
Abstract The European crisis emerged in 2008 and got worse in 2009. Triggers the onset of European crisis is because Greece has defaulted on debt. The Government of Greece that is already too much owed finally dragged the countries in the European Union into a terrible crisis. Turkey, as one of the country's largest trading partner Europe also dragged into crisis in Europe. That impact affected  the economic growth of Turkey which previously showed positive growth. The resolving crisis done Turkey have in common with the way the Prophet in the developing economy of Medina when the early Muslims doing Hijra from Makkah to Medina in the year 622-623. The author tried to compare the strategies of Prophet and Turkey in tackling the impact of the crisis and build the economy of the country so as to successfully compete in the global market. The purpose of this research is to provide an overview of knowledge how Turkey to cope with the impact of the European economic crisis  and became one of the countries with good economic growth in the future compared with the strategies of Prophet in building the economy of Medina. This research using the method of comparative analysis in comparing Turkey's strategy in tackling the crisis and strategies of Prophet in the developing economy of Medina. While the data collection method used is by way of a research library (library research). Library Research is looking for a wide range of information, news analysis, concepts of experts thought the result embodied in books, journals, articles, internet, print-related themes. Research results based on research libraries prove that the strategy that carried Turkey to cope with the impact of the economic crisis in Europe have in common with the strategies of Prophet Muhammad in building the economy of Medina. By utilizing natural resources, building new markets and do political contracts with neighboring countries and played an important role in regional politics and make useful of the strategic location of the country, Turkey managed to cope with the impact of the European crisis and this strategy into solutions that are able to bring Turkey to the brink of success in building the economy of the country. Key Words: European Crisis, Turkey’s Economy, Strategy of Rasulullah, Comparative Study